Unmanned aerial vehicle (UAV) for indoor social event - Huang, Desmond Bao Feng (2015)
Humans are more curious about objects that levitate. We are often fascinated and keen to try it out. In recent years there is an increasing population growth of UAV applications in the outdoor environment. So is it applicable for indoor purposes? Lesser possibility to try out indoor due to several reasons like limited flying spaces, higher risks of damages and greater precise control of UAV within enclosed areas. The successful impact will give mobility to the current indoor surveillance and greater angle of view of photography or videography. The focus is to provide an indoor flying platform, with safety as priority for entertainment and event requirement. In order to build up the confidence level of our audience, multiple experiments of testing and flight must be conducted to reduce the risk of air crash. Planning and prototype testing is essential to minimise equipment loss and furthermore enclosed safety netting area will help to prevent any unpredictable situation that may happen. In addition with the help of schematic diagram and analytic models, wire connections are done neatly and accurately. There is this psychological factor, which contributes to the belief of the UAV being able to carry out its mission. It takes time to persuade our audience what they are watching is safe, just like our aviation industry. Nevertheless the fascination that UAV applications bring good future in replacing certain job processes and reduces the danger in capturing photos or videos in a more unsafe position. The key advantages, comparing to the bigger size UAV, are cost saving, more resource usage effective and lower damage and danger risk.